The large mammal fossil fauna of the Cradle of Humankind, South Africa: a review - Megan Malherbe; Robyn Pickering; Deano Stynder; Martin Haeusler (PeerJ)
South Africa’s Cradle of Humankind UNESCO World Heritage Site has remained the single richest source of hominin fossils for over ninety years. While its hominin specimens have been the subject of extensive research, the same is not true for its abundant faunal assemblages, despite their value in Plio-Pleistocene palaeoenvironmental reconstructions. Moreover, precise ages and depositional histories have been historically difficult to assess, though advancements in both relative and absolute dating techniques are changing this. This review explores the history of non-hominin large mammal faunal reporting, palaeoenvironmental reconstructions based on these fauna, and dating histories (with a focus on biochronology) at the following eight fossil-bearing sites of the Cradle that have been radiometrically dated with uranium-lead: Bolt’s Farm, Cooper’s Cave, Drimolen, Haasgat, Hoogland, Malapa, Sterkfontein and Swartkrans. Continued efforts to provide more precise and direct ages for sites using a variety of methods indicate that the bulk of Cradle deposits date to between 3 and 1.4 Ma. We find that, across almost all eight sites, there is little discussion or debate surrounding faunal reports, with some sites described by a single publication. Many of the reports are decades old with little review or reanalysis in the years following, emphasising the need for reviews such as this one. Our analysis of the data indicates that faunal-based paleoenvironmental reconstructions across sites commonly show a trend of wooded landscapes giving way to grasslands. We find that these reconstructions are primarily based on faunal abundance data, despite the availability of many other informative analytical techniques. The findings of this review highlight a need for more extensive and robust faunal reporting, as this will aid in understanding the context of these Cradle sites.